2014
DOI: 10.1042/bj20140235
|View full text |Cite|
|
Sign up to set email alerts
|

DJ-1 interacts with RACK1 and protects neurons from oxidative-stress-induced apoptosis

Abstract: PD (Parkinson's disease) is a complex disorder that is associated with neuronal loss or dysfunction caused by genetic risks, environmental factors and advanced aging. It has been reported that DJ-1 mutations rendered neurons sensitive to oxidative damage, which led to the onset of familiar PD. However, the molecular mechanism is still unclear. In the present study we show that DJ-1 interacts with RACK1 (receptor of activated C kinase 1) and increases its dimerization and protein stability. The DJ-1 transgene p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…), induces oxidative stress (Ma et al . ) and represents a reasonable pathophysiological level of H 2 O 2 (Lei et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), induces oxidative stress (Ma et al . ) and represents a reasonable pathophysiological level of H 2 O 2 (Lei et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…), and Ma and coworkers reported that 50 μM H 2 O 2 induces oxidative stress in DIV6 cortical neurons (Ma et al . ). Therefore, in this study, we selected 40 μM H 2 O 2 as the best approximation of a pathophysiological relevant and oxidative stress‐inducing level of H 2 O 2 .…”
Section: Methodsmentioning
confidence: 97%
“…RACK1 was originally identified as an intercellular scaffold protein of the Trp-Asp (WD) repeat protein family (23). RACK1 can recruit and bind many kinases and receptors, such as PKC and DJ-1, thereby impacting a wide range of signal transduction pathways (24,25). RACK1 plays an important role in multiple cellular functions, including cell growth, migration and differentiation (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…RACK1 was originally identified to bind and activate protein kinase C and is now recognized as a multi-functional scaffold protein (11,12). Evidence has indicated that RACK1 protects from oxidative stress-induced cell death in various types of cells, including fission yeasts (13), shrimp cells (14), neurons (15), HeLa cells (16) and HL60 cells (17). However, such a role for RACK1 has not been reported in HCC cells to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 76%